Gasdermin D could be lost in the brain parenchyma infarct core and a pyroptosis-autophagy inhibition effect of Jie-Du-Huo-Xue decoction after stroke - Chang Zhou; Chang Zhou; Chang Zhou; Shi-wei Qiu; Shi-wei Qiu; Feng-ming Wang; Yu-chen Liu; Yu-chen Liu; Wei Hu; Mei-lan Yang; Wang-hua Liu; Wang-hua Liu; et al. (Frontiers Media S.A., 2024)
BackgroundThe Chinese ethnic medicine Jie-Du-Huo-Xue Decoction (JDHXD) is used to alleviate neuroinflammation in cerebral ischemia (CI). Our previous studies have confirmed that JDHXD can inhibit microglial pyroptosis in CI. However, the pharmacological mechanism of JDHXD in alleviating neuroinflammation and pyroptosis needs to be further elucidated. New research points out that there is an interaction between autophagy and inflammasome NLRP3, and autophagy can help clear NLRP3. The NLRP3 is a key initiator of pyroptosis and autophagy. The effect of JDHXD promoting autophagy to clear NLRP3 to inhibit pyroptosis on cerebral ischemia-reperfusion inflammatory injury is currently unknown. We speculate that JDHXD can inhibit pyroptosis in CI by promoting autophagy to clear NLRP3.MethodsChemical characterization of JDHXD was performed using LC-MS. Model of middle cerebral artery occlusion/reperfusion (MCAO/R) was established in SD rats. Neurological deficits, neuron damage, and cerebral infarct volume were evaluated. Western Blot and immunofluorescence were used to detect neuronal pyroptosis and autophagy.Results30 possible substance metabolites in JDHXD medicated serum were analyzed by LC-MS (Composite Score > 0.98). Furthermore, JDHXD protects rat neurological function and cerebral infarct size after CI. JDHXD inhibited the expression of pyroptosis and autophagy after CI. Our western blot and immunofluorescence results showed that JDHXD treatment can reduce the expression of autophagy-related factors ULK1, beclin1, and LC3-Ⅱ. The expression of NLRP3 protein was lower in the JDHXD group than in the I/R group. Compared with the I/R group, the expressions of pyroptosis-related factors caspase-1 P 10, GSDMD-NT, IL-18, and IL-1β decreased in the JDHXD group. Furthermore, we observed an unexpected result: immunofluorescence demonstrated that Gasdermin D (GSDMD) was significantly absent in the infarct core, and highly expressed in the peri-infarct and contralateral cerebral hemispheres. This finding challenges the prevailing view that GSDMD is elevated in the ischemic cerebral hemisphere.ConclusionJDHXD inhibited pyroptosis and autophagy after MCAO/R. JDHXD suppressed pyroptosis and autophagy by inhibiting NLRP3, thereby alleviating CI. In addition, we present a different observation from previous studies that the expression of GSDMD in the infarct core was lower than that in the peri-infarct and contralateral non-ischemic hemispheres on day 3 of CI.